A Differential Evolution Approach for Reduced Order Frequency Response Models Identification - Inostroza-Ponta, M; Chavez-Orostica, H; Villalobos-Cid, M; Quiroz-Moreno, J; Fernandez-Goycoolea, J (Institute of Electrical and Electronics Engineers Inc., 2023)
Reduced order frequency response models have been used as an alternative to simulate the behavior of the electrical system during limited time intervals corresponding to contingencies of the system. This paper presents four model alternatives of this kind and a proposed methodology for their parameter identification. Specifically, the differential evolution algorithm is considered and tested experimentally over data from the Chilean electrical network. Emphasis of the study is placed on the proposed methodology s implementation aspects, advantages, and potential problems. © 2023 IEEE.